Clinically Significant Fatigue: Prevalence and Associated Factors in an International Sample of Adults with Multiple Sclerosis Recruited via the Internet - Weiland, Tracey J. (PLoS One, 2015)
BACKGROUND: Fatigue contributes a significant burden of disease for people with multiple sclerosis (PwMS). Modifiable lifestyle factors have been recognized as having a role in a range of morbidity outcomes in PwMS. There is significant potential to prevent and treat fatigue in PwMS by addressing modifiable risk factors. OBJECTIVES: To explore the associations between clinically significant fatigue and demographic factors, clinical factors (health-related quality of life, disability and relapse rate) and modifiable lifestyle, disease-modifying drugs (DMD) and supplement use in a large international sample of PwMS. METHODS: PwMS were recruited to the study via Web 2.0 platforms and completed a comprehensive survey measuring demographic, lifestyle and clinical characteristics, including health-related quality of life, disability, and relapse rate. RESULTS: Of 2469 participants with confirmed MS, 2138 (86.6%) completed a validated measure of clinically significant fatigue, the Fatigue Severity Scale. Participants were predominantly female from English speaking countries, with relatively high levels of education, and due to recruitment methods may have been highly pro-active about engaging in lifestyle management and self-help. Approximately two thirds of our sample (1402/2138; 65.6% (95% CI 63.7–67.7)) screened positive for clinically significant fatigue. Bivariate associations were present between clinically significant fatigue and several demographic, clinical, lifestyle, and medication variables. After controlling for level of disability and a range of stable socio-demographic variables, we found increased odds of fatigue associated with obesity, DMD use, poor diet, and reduced odds of fatigue with exercise, fish consumption, moderate alcohol use, and supplementation with vitamin D and flaxseed oil. CONCLUSION: This study supports strong and significant associations between clinically significant fatigue and modifiable lifestyle factors. Longitudinal follow-up of this sample may help clarify the contribution of reverse causation to our findings. Further research is required to explore these associations including randomized controlled trials of lifestyle interventions that may alleviate fatigue.